Successful Split Thickness Skin Graft In Stable Vitiligo Not Responding To Autologous Miniature Skin Grafts - Malakar Subrata (Wolters Kluwer Medknow Publications, 1997)
Surgical replacements of stable vitiligo with pigmented skin is an effective alternative for patients. But none of them is fully dependable as they induce satisfactory repigmentation with some drawbacks. One such is the occasional depigmentation of the minigrafts. Split thickness skin grafting (STSG) has been tried in cases not responding to autologous miniature punch grafts. A series of 7 patients with 10 localised, stable, refractory and minigraft-failure patches was treated institutionally by dermabrasion and STSG and followed up for 16 months. The graft take was 100% in 7 patches and 90% in the remaining 3 and 100% repigmentation was achieved in 4 cases, 95% in 2 cases and 90% in 1. Time taken for satisfactory colour match varied 4.5 to 8.5 months. Complications were minor and did not affect the results. Stable and refractory patches of vitiligo, not responding to autologous miniature punch grafts, can be treated by STSG with good to excellent repigmentation.